In-depth interview guide on stakeholders' perceptions of the Baxnaano Safety Net Program benefits in Somalia - Bliznashka, Lilia; Nwabuikwu, Odiche; Diatta, Ampa Dogui; Gelli, Aulo; Magan, Mohamed; Hassan, Hashi (International Food Policy Research Institute, 2024)
A guide designed to assess stakeholders' views on the program benefits, fidelity of implementation, implementation challenges, and the feasibility of its next phase.